Type-specific effects of orofacial pain on sleep quality: a cross-sectional clinical study - Cosgun-Baybars, Sumeyye; Talu, Merve Hacer; Yalcin, Hacer; Gokdemir, Dicle (Mre Press, 2026)
Background: This study aimed to assess the impact of different types of orofacial pain on sleep quality and to examine the influence of age and gender on sleep-related parameters. Methods: In this cross-sectional study, 400 patients with orofacial pain presenting to the Faculty of Dentistry, F & imath;rat University, were included. Participants were divided into eight pain categories: pulpal, periodontal, impacted tooth-related, dental implant-related, temporomandibular disorder-related, mucosal/cutaneous, neuropathic, and oncologic. Pain intensity was measured using the Numeric Rating Scale, and sleep quality was assessed via the Pittsburgh Sleep Quality Index (PSQI). Non-parametric tests and correlation analyses were used for statistical evaluation. Results: The mean age was 33.62 +/- 13.06 years, and 66.8% were female. The mean global PSQI score was 5.56 +/- 2.84. Neuropathic and mucosal/cutaneous pain groups demonstrated significantly higher PSQI scores, especially in sleep latency and disturbances (p < 0.05). Females had significantly higher scores in sleep latency, disturbances, and daytime dysfunction than males (p <0.05). Age was weakly but significantly correlated with several PSQI components. Conclusions: Neuropathic and mucosal/cutaneous pain types were associated with the most detrimental effects on sleep quality. Gender and age were also found to influence specific sleep parameters.
Keywords: Orofacial pain; Sleep quality; Pittsburgh sleep quality index; Neuropathic pain; Temporomandibular disorders